Efficacy of clozapine for long‐stay patients with treatment‐resistant schizophrenia: 4‐year observational study. Issue 2 (2nd March 2022) - Mizuno, Kentaro; Mizuno, Emiko; Suekane, Akira; Shiratsuchi, Toshiaki
Abstract: Aim: Supporting patients upon discharge following prolonged hospitalization in private psychiatric hospitals in Japan have long been an issue. This study evaluated the efficacy of clozapine in treating long‐stay patients with treatment‐resistant schizophrenia to reduce the frequency and duration of readmissions postdischarge. Methods: We retrospectively examined the length and frequency of hospitalizations of long‐stay and non‐long‐stay patients with schizophrenia who were introduced to clozapine at our hospital. Results: Comparing participants' medical records 2 years before and after the introduction of clozapine, we identified a significant decrease in both length and frequency of hospitalizations in all patients who were introduced to clozapine. In long‐stay patients, the length and frequency of hospitalization were significantly reduced. However, compared to non‐long‐stay patients, the period from introduction of clozapine to discharge was longer and the dose of clozapine was higher. Thus, it is necessary to take time to evaluate the therapeutic effects for long‐stay patients. Conclusion: The results showed that clozapine is helpful for patients with treatment‐resistant schizophrenia, who are considered difficult to treat and discharge in Japan. Abstract : We retrospectively examined the length and frequency of hospitalizations of long‐stay and non‐long‐stay patients with schizophrenia who were introduced to clozapine at our hospital. Two years before and after the introduction of clozapine, we identified a significant decrease in both length and frequency of hospitalizations in all patients who were introduced to clozapine.